Examining Students’ Thoughts on Climate Change in the Context of Basic Concept - DOĞRU, Said; YÜZBAŞIOĞLU, Fatih (Research on Education and Psychology, 2023)
In this study, our aim was to investigate the beliefs of middle school students about climate change. We conducted study with 183 secondary school students. Within the scope of the study, students were asked two questions about climate change, and written responses were analyzed using an embedded a mixed-method approach. The questions posed were: (1) What is the cause of global warming? (2) What factors influence the climate? Based on the results of the quantitative analysis of the participants' responses, the answers to the first question were "human," "greenhouse effect," and "Earth." The concepts of "pollution," "atmosphere," and "Earth" are used in the second question. As per the qualitative analysis results, the students' responses focused on three elements: "living things, Earth, and atmosphere." The students responses to the second question reveal a more specific or general attitude. The findings indicate that students view climate change not merely as an isolated phenomenon but as a complex system influenced by various components. It is also suggested that students have an understanding of the distinction between weather and climate. The ability to connect climate change with social issues may encourage individuals to make greater efforts in mitigating its effects.
Keywords: Eğitim Psikolojisi; Educational Psychology; Climate literacy; Climate change; Beliefs of middle school students; 13. Climate action; 4. Education